O maestro, a orquestra e a racionalização das práticas musicais - Neylson Joao Batista Filho (2015)
This dissertation aims to describe and analyze the modern orchestra development and its internal relations as well as the modern conducting technique development, explaining how this practices evidence the rationalization process as exposed by Weber in his work The rational and social foundations of music. After the presentation of the orchestra and description of its development, we analyzed how it evidences the rationalization of this specific musical practice. The same was done with the modern conducting technique. Then, we analyzed the irrational aspects intrinsic in the gestural choosing process involved in the left hand performance. Finally, one can observe that the three elements that compose the conducting technique the right hand, the left hand and the facial-bodily expressions have different rationalization levels.